Review: Eicosanoids in preterm labor and delivery: Potential roles of exosomes in eicosanoid functions. (June 2017) - Peiris, H.N.; Vaswani, K.; Almughlliq, F.; Koh, Y.Q.; Mitchell, M.D.
Abstract: Preterm delivery is a major obstetric health problem contributing to poor neonatal outcome including low birth weight, respiratory distress syndrome, gastrointestinal, immunologic, central nervous system, hearing, and vision problems. Worldwide, approximately 15 million babies are born prematurely each year. The critical question which remains is how to identify women destined to deliver preterm from those who will achieve a term delivery. Prostaglandins, in all mammals, are important in the parturient process. Increased intrauterine prostaglandin production is associated with labor and in fact prostaglandin E2 (PGE2 ) or analogs are widely used clinically for cervical ripening and labor induction. Measurements of circulating eicosanoids have been problematic because of the rapid and major clearance by the lungs and then kidneys resulting in very low concentrations in plasma. Moreover, since eicosanoids are produced by all mammalian tissues, the sources of the measured eicosanoids are unknown. Our understanding of how cells communicate has undergone a paradigm shift with the recognition of the role of exosomes in intercellular signaling. Recent publications have identified enzymes and products of arachidonic acid metabolism (eicosanoids) within exosomes. This review will explore the potential roles of exosomes in eicosanoid functions that are critical in preterm labor and delivery.